The pH dependence of NADPH oxidase in human eosinophils - Morgan, Deri (Blackwell Science Inc, 2005)
NADPH oxidase generates reactive oxygen species that are essential to innate immunity against microbes. Like most enzymes, it is sensitive to pH, although the relative importance of pH(o) and pH(i) has not been clearly distinguished. We have taken advantage of the electrogenic nature of NADPH oxidase to determine its pH dependence in patch-clamped individual human eosinophils using the electron current to indicate enzyme activity. Electron current stimulated by PMA (phorbol myristate acetate) was recorded in both perforated-patch configuration, using an NH(4)(+) gradient to control pH(i), and in excised, inside-out patches of membrane. No electron current was detected in cells or excised patches from eosinophils from a patient with chronic granulomatous disease. When the pH was varied symmetrically (pH(o) = pH(i)) in cells in perforated-patch configuration, NADPH oxidase-generated electron current was maximal at pH 7.5, decreasing drastically at higher or lower values. Varying pH(o) and pH(i) independently revealed that this pH dependence was entirely due to effects of pH(i) and that the oxidase is insensitive to pH(o). Surprisingly, the electron current in inside-out patches of membrane was only weakly sensitive to pH(i), indicating that the enzyme turnover rate per se is not strongly pH dependent. The most likely interpretation is that assembly or deactivation of the NADPH oxidase complex has one or more pH-sensitive steps, and that pH-dependent changes in electron current in intact cells mainly reflect different numbers of active complexes at different pH.